The Efficacy of Fluoride in Reducing Tooth Decay: A Systematic Review of Evidence-Based Interventions - Khallaf, Ahmed Mohammed Ahmed; Rais, Rayan Amro; Naamani, Sari Nabil; Almalki, Alaa Mushref; Alyamani, Majid Nooraldeen; Felemban, Firas Fawaz; Alhajrassi, Sahar Khalil; Felemban, Anas Fawaz; gattan, Hazem Ahmed; Marir, Marwan Mohammed (Journal of Ecohumanism, 2024)
Tooth decay, a significant global public health issue, affects billions of individuals and imposes substantial health and economic burdens. Fluoride has been widely recognized for its caries-preventive properties, functioning through mechanisms that enhance enamel remineralization and inhibit bacterial activity. Despite extensive research supporting its efficacy, variations in fluoride delivery methods, concentrations, and population-specific outcomes have resulted in inconsistent findings, necessitating a comprehensive review. This study systematically evaluates recent evidence to determine fluoride’s effectiveness in reducing tooth decay across various applications, including water fluoridation, toothpaste, mouth rinses, and professional treatments. By synthesizing data from peer-reviewed studies, the review aims to clarify optimal fluoride use practices and address safety concerns, such as dental fluorosis. Findings are expected to provide actionable insights for clinicians, policymakers, and public health professionals, contributing to the development of evidence-based guidelines to improve global oral health and reduce the burden of dental caries.